(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In the article, measures aimed at meeting social needs and the intellectual needs of adolescents can serve as a means of preventing Internet addiction in adolescents. The article provides methodological recommendations for the prevention of adolescent computer addiction.